The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/cid.13056
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different forms of sinus membrane perforation on the prevalence of postoperative complications in lateral window sinus floor elevation: A retrospective study

Abstract: Background Maxillary sinus membrane perforation (SMP) during lateral window sinus floor elevation (SFE) might be associated with postoperative complications (PC). Objectives To evaluate the prevalence of PC and clinical implant outcome for different forms of SMP with lateral window SFE. Material and Methods The prevalence of PC such as maxillary sinusitis, graft necrosis and wound infection was retrospectively evaluated for 434 lateral window SFE (334 patients) with 331 SFE (241 patients) without and 103 SFE (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Despite thorough preoperative evaluation, antibiotic prescription before and after surgery, proper surgical technique, appropriate postoperative care, and patient education, sinusitis remained a concern. Similar to our study, Kahnberg and Vannas-Löfqvist (2008) and Krennmair et al (2022) reported a high incidence of sinusitis (9.7%-22%) in patients undergoing maxillary sinus augmentation.…”
Section: Restoysupporting
confidence: 91%
“…Despite thorough preoperative evaluation, antibiotic prescription before and after surgery, proper surgical technique, appropriate postoperative care, and patient education, sinusitis remained a concern. Similar to our study, Kahnberg and Vannas-Löfqvist (2008) and Krennmair et al (2022) reported a high incidence of sinusitis (9.7%-22%) in patients undergoing maxillary sinus augmentation.…”
Section: Restoysupporting
confidence: 91%
“…Thus, the Schneiderian membrane biotype and the size of perforation were essential to evaluate the risk of postoperative complications in maxillary sinus floor elevation. 36 Lining in the inner part of the maxillary sinus cavities, the blood supply of Schneiderian membrane is derived from the anastomoses of the infraorbital artery and the posterior superior alveolar artery. 37 The sinus membrane is characterized by a periosteum overlaid with a layer of pseudostratified ciliated epithelium and the underlying highly vascularized connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Not only as a physical barrier and maintains the normal function of the sinus, the integrity of the sinus membrane but also provides blood supply and osteogenic potential to enhance the graft maturation. Thus, the Schneiderian membrane biotype and the size of perforation were essential to evaluate the risk of postoperative complications in maxillary sinus floor elevation 36 . Lining in the inner part of the maxillary sinus cavities, the blood supply of Schneiderian membrane is derived from the anastomoses of the infraorbital artery and the posterior superior alveolar artery 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Krennmair and colleagues showed no differences regarding implant survival rates between LWSFA sites with (99.1%) and without (99.5%) perforations. 28 As a matter of fact, the reported prevalence of postoperative complications (e.g., maxillary sinusitis, graft necrosis) was highly correlated to presence of large sinus perforations within a thin SMT (OR = 18.04) but not to sex, smoking, presence of sinus septa and/or surgical stage. This is in accordance with the findings of this study as sinus perforations were observed (5 out of 24 LWSFA sites) and had no impact upon implant survival rates or onset of postoperative complications.…”
Section: Volumetric Analysismentioning
confidence: 94%